Carreiras docente e técnico administrativa em educação: o olhar desses sujeitos coletivos e a análise de suas relações hierárquicas e de trabalho em uma Universidade Federal - Silva, Liane Specke da (Universidade do Vale do Rio dos Sinos, 2018)
The purpose of this research is to present the characteristics of the careers of teachers and administrative technicians in education of the Federal Institutions of Higher Education in Brazil, investigate if there are hierarchical relationships between these different careers, based on what the legislation provides, and also analyze the scope of the IFES, especially for the Federal University of Rio Grande do Sul (UFRGS), using the Collective Subject Discourse (DSC) method. This research can be classified as historical-documentary, since it sought to ascertain and order the historical documents and the legislation that covers the teaching and technical-administrative careers in education, in the scope of the Brazilian federal universities, analyzing the nature of the hierarchical relationships existing between both. In addition, as a complement to documentary research, a semi– structured qualitative research was carried out to understand the convergences and divergences between what precepts the legislation about the hierarchical line between careers and how it is carried out day by day in practice. Two data analysis criteria were used: as far as the legislation was concerned, the analysis was historical-documentary; in relation to the data collected from the research, the Discourse of the Collective Subject (DSC) methodology was used. As a result of the research and the elaborated DSCs, some proposals were made directed to the IFES and its employees, among them the one of greater valorization of its human resources, in particular theTAEs, the necessity of professionalization and qualification of the academic managers, the possibility of technicians to assume managerial positions in the IFES and improve the organization at the environment by elimination of partisanization, transforming the internal structure and developing a new context of labor relations, eliminating corporatism, conservatism and individualism.
Keywords: Docentes; Técnicos; Administrativos em Educação; Hierarquia; Discurso do sujeito coletivo; IES; Teachers; Technical; Administrative in Education; Hierarchy; Discourse of the collective subject; IES; Administrativos em Educação; ACCNPQ::Ciências Humanas::Educação